POLA PEMBAHARUAN PENDIDIKAN ISLAM DI TURKI - NIA WARDHANI (AZKIA : Jurnal Aktualisasi Pendidikan Islam, 2020)
The notion of renewal of Islamic education has a lot to do with the idea of ​​renewing Islamic thought and institutions as a whole. In other words, the renewal of Islamic education cannot be separated from the rise of Islamic renewal ideas and programs. This is because the basic framework behind Islamic reform as a whole is that Islamic thought and institutions are prerequisites for the rise of Muslims in modern times. Without an overhaul of thought as explained, no other form of reform can be realized. By taking into account several factors which are the cause of the birth of Islamic education renewal, according to the authors, in outline there have been two thoughts on the renewal of Islamic education, both patterns are: 1. The pattern of Islamic education renewal which is oriented towards modern educational patterns in the West, which later became known as modernist movement, and 2. Renewal of Islamic education oriented towards the aim of refining Islamic teachings.